2021
DOI: 10.1186/s12888-021-03456-z
|View full text |Cite
|
Sign up to set email alerts
|

Depression, post-traumatic stress, anxiety, and fear of COVID-19 in the general population and health-care workers: prevalence, relationship, and explicative model in Peru

Abstract: Background This study has two aims. First, determine the fit of the fear model to COVID-19, anxiety, and post-traumatic stress in the general population and health-care workers. Second, determine which model best explains the relationship between depression and the triad of fear, anxiety, and post-traumatic stress in both groups. Method A cross-sectional study was conducted using self-reported questionnaires for anxiety, fear of COVID-19, depressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
1
13
0
1
Order By: Relevance
“…This may be due to that study having been conducted one month after the declaration of a state of emergency in the United States for COVID-19, when the epidemic was still progressing at a high level, whereas our study was conducted when the epidemic was largely under control. We observed that the prevalence of PTSD symptoms in college students was lower than the yields of studies performed during the COVID-19 outbreak, while anxiety and depressive symptoms were in line with or higher than them [ 22 , 23 , 24 , 25 ]. Prior research identified a higher prevalence of mental health symptoms reported by students than the overall population due to multiple concerns about academic delays, financial support, reduced social relationships, etc.…”
Section: Discussionmentioning
confidence: 75%
“…This may be due to that study having been conducted one month after the declaration of a state of emergency in the United States for COVID-19, when the epidemic was still progressing at a high level, whereas our study was conducted when the epidemic was largely under control. We observed that the prevalence of PTSD symptoms in college students was lower than the yields of studies performed during the COVID-19 outbreak, while anxiety and depressive symptoms were in line with or higher than them [ 22 , 23 , 24 , 25 ]. Prior research identified a higher prevalence of mental health symptoms reported by students than the overall population due to multiple concerns about academic delays, financial support, reduced social relationships, etc.…”
Section: Discussionmentioning
confidence: 75%
“… 9 , 14 , 15 , 16 , 17 , 18 , 19 Additionally, these studies have also examined factors associated with mental illnesses in COVID-19 patients. Limited access to health care, having pre-existing comorbidities, general health, 15 , 16 , 17 , 18 employment and economic status, 19 , 20 , 21 marital status, 15 , 16 , 22 being female, 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 27 and education 20 , 28 , 29 have been identified as associated factors of depression, anxiety and stress in COVID-19 patients in general population.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health afflictions caused by the pandemic are more frequent in vulnerable groups such as children, elders, frontline workers, people with pre-existing mental pathologies, and, more specifically, individuals who recovered from COVID-19 [6,7]. In this last group, depression, anxiety, posttraumatic stress, and poor sleep quality persist for several months after hospital discharge [8][9][10].…”
Section: Introductionmentioning
confidence: 99%